Productive performance of broilers fed cassava meal (Manihot esculenta) as maize replacement - Celis P., William (2019)
The aim of this study was to determine the productive performance of broilers fed cassava meal (Manihot esculenta) as partial replacement of maize in the finishing stage. A total of 96 broiler chickens of the 21-day-old Cobb line were used, distributed in 12 experimental pens corresponding to three treatments with four repetitions. The substitution levels of maize for cassava meal were 0, 10 and 20%, which represented the treatments T0 (control), T1 and T2, respectively. Each treatment had 32 chickens and each repetition eight chickens. The effect of cassava flour on feed consumption, weight gain, feed conversion, mortality and productive efficiency index was evaluated. No significant differences were found between treatments in the evaluated indicators, indicating that cassava meal can effectively replace up to 20% in broiler maize-based diets.